A conceptual framework for road traffic safety considering differences in traffic culture through international comparison. (April 2022) - Morimoto, Aikinori; Wang, Ailin; Kitano, Naohiro
Abstract: Many countries and international organizations have put a significant amount of effort into improving road traffic safety by setting their own road traffic safety goals and strategies. This study aims to provide a conceptual framework for road traffic safety through an international comparison of traffic safety goals and strategies. Such a comparison can help improve mutual understanding and communication among stakeholders in different countries and international organizations. Based on a review of previous traffic safety literature and comparing traffic safety strategies of several different countries and international organizations, this study proposes a conceptual framework for road traffic safety consisting of a common vision, traffic safety indicators, a safe system including the 3Es and some additional Es, and a traffic safety culture, which is the basis of the framework. Highlights: Different road traffic safety strategies are discussed and compared. Besides engineering, education, and enforcement (3Es), other Es such as emergency response system need to be emphasized. A common conceptual framework for future road traffic safety development is proposed. Conceptual framework comprises common vision, safety indicators, safe system with "3Es+ α ", and traffic safety culture.